The African Union : legal and institutional framework, a manual on the Pan-African Organization / edited by Abdulqawi A. Yusuf and Fatsah Ouguergouz. - Yusuf, Abdulqawi (Martinus Nijhoff Pub. : Brill, 2012)
This work is an introduction into the origins, law and institutions of the African Union (AU). It examines the evolution, structures, legal standards and operational activities of this Pan-African organization, which replaced the Organization of African Unity (OAU) ten years ago.